Differences in management and treatment of traumatic adult pan brachial plexus injuries: a global perspective regarding continental variations. (January 2022) - Shin, Alexander Y.; Socolovsky, Mariano; Desai, Ketan; Fox, Michael; Wang, Shufeng; Spinner, Robert J.
An expert opinion study was designed to query five countries and six brachial plexus surgeons regarding the demographics, mechanisms of injury, evaluation, timing of surgery, reconstructive strategies and controversies in adult traumatic pan brachial plexus injuries. Variations in assessing outcomes, management of neuropathic pain and future considerations were elucidated. Clear differences in regional demographics, mechanisms of injury, patient evaluation and treatment strategies were identified. The role of phrenic nerve and contralateral C7 transfer, acute use of free functioning muscle transfers, root reimplantation and amputation/myoelectric prosthetic fitting were regional/surgeon dependent. Comparison of outcomes across regions requires an understanding of the regional nuances of patient demographics, injury mechanisms, preferred reconstructive strategies and how outcomes are measured. Future studies are required to allow accurate regional comparisons.